Analysis of errors in subject-verb agreement among Malaysian ESL learners - Siti Hamin Stapa,; Mohd Mustafa Izahar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
This article analyses errors on subject-verb agreement among post-graduate teacher trainees in a college in Malaysia. Twenty postgraduate (English Language Studies) students from a teachers’ training college from the northern state of Malaysia participated in the study. The study examined errors in 5 types of subject-verb agreements: person,number, coordinated subject, indefinite expression of amount and also notional agreement and proximity. 2 types of written compositions (argumentative and factual)were analyzed to identify the problems in writing grammatically correct subject-verb agreement by the students. The results of the study reveal that the majority of the students commit errors in subject-verb agreement, especially in SVA of number followed by SVA of person. The students were found to avoid using the complex sub-rules of SVA that include the agreement with coordinated subject, agreement with indefinite expressions of amount and also notional agreement and proximity.